(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Abstract: Speaking competence is a fundamental aspect of English language learning that significantly influences students’ academic and professional success. Traditional teaching methods often do not provide sufficient opportunities for interactive speaking practice or personalized feedback. The integration of Artificial Intelligence (AI) in language education offers innovative solutions to these challenges. AI software can enhance students’ speaking abilities by providing real-time feedback, adaptive learning paths, and interactive conversational experiences. This article explores the theoretical foundations of speaking competence, reviews the role of AI in English teaching, and discusses practical approaches to effectively incorporate AI tools in the classroom.